The association between the introduction of quantitative assessment of postpartum blood loss and institutional changes in clinical practice: an observational study. (May 2020) - Katz, D.; Wang, R.; O'Neil, L.; Gerber, C.; Lankford, A.; Rogers, T.; Gal, J.; Sandler, R.; Beilin, Y.
Highlights: Quantitative assessment of blood loss (QBL) systems are available. Introduction of a QBL system suggested differences compared with simple estimation of blood loss. Differences were in the timing and volume of peripartum blood loss. Recognition of postpartum haemorrhage was enhanced but blood loss lower. Differences in outcomes associated with QBL varied according to mode of delivery. Abstract: Background: Imprecise visual estimates of blood loss contribute to morbidity from postpartum hemorrhage. We examined the impact of quantitative assessment of postpartum blood loss on clinical practice and outcomes. Methods: An observational study comparing blood loss, management and outcomes between two historical cohorts (August 2016 to January 2017 and August 2017 to January 2018) at an academic tertiary care center. Patients in the intervention group (second period) had blood loss quantified compared with visual estimation for controls. Results: We included 7618 deliveries (intervention group n=3807; control group n=3811). There was an increase in the incidence of hemorrhage (blood loss >1 L) in the intervention group for both vaginal (2.2% vs 0.5%, P  <0.001) and cesarean delivery (12.6% vs 6.4%, P  <0.001). There was also a difference in median blood loss for vaginal (258 mL [151–384] vs 300 mL [300–350], P  <0.001); and for cesarean delivery (702 mL [501–857] vs 800 mL [800–900], P  <0.001). The median red blood cell units transfused was different in the intervention group having cesarean delivery (2 units [1–2] vs 2 units [2–2], P =0.043). Secondary uterotonic usage was greater in the intervention group for vaginal (22% vs 17.3%, P  <0.001) but not cesarean delivery (7.0% vs 6.0%, P =0.177). Laboratory costs were different, but not the re-admission rate or length of stay. Conclusions: Quantifying blood loss may result in increased vigilance for vaginal and cesarean delivery. We identified an association between quantifying blood loss and improved identification of postpartum hemorrhage, patient management steps and cost savings.